ELECTROSTATIC MASSAGE AND RADONOTHERAPY IN REHABILITATION OF VIBRATION NEUROPATHY PATIENTS - Раиса Васильевна Гордеева (Medicina v Kuzbasse, 2019)
Objective. The research objective is studying effective methods of rapid recovery of motor functions and sensitivity due to early relief of pain syndrome, prevention of formation of joint contractures, improvement of peripheral nerve conduction in vibration disease patients during rehabilitation based on the use of radon baths and electrostatic massage.